THE INFLUENCE OF CONFORMITY ON BULLYING BEHAVIOR: THE MEDIATING ROLE OF CRITICAL THINKING - Juandina, Anita Mestika; Dewi, Salamiah Sari; Indrawan, Yudistira Fauzy (Pena Cendekia Insani, 2026)
Bullying remains a serious problem in schools and is often influenced by peer conformity among adolescents. This study aims to examine the effect of conformity on bullying behavior and the mediating role of critical thinking among students of SMA Budi Agung Medan. A quantitative approach was used involving 117 students selected through cluster random sampling. Data were collected using conformity, bullying behavior, and critical thinking scales and analyzed using Structural Equation Modeling (SEM). The results showed that conformity had a positive and significant effect on bullying behavior and a negative effect on critical thinking. Critical thinking also had a negative and significant effect on bullying behavior and significantly mediated the relationship between conformity and bullying. These findings indicate that higher conformity increases the likelihood of bullying, while stronger critical thinking reduces such behavior. Strengthening students’ critical thinking may serve as an effective strategy to prevent bullying in schools.